Patient Decision Making in the Choice of a Referral Hospital in Hospital of Subulussalam City in 2018 - Siti Latifah Hanum; Destanul Aulia; Kintoko Rochadi (Britain International of Exact Sciences (BIoEx) Journal, 2020)
The choice of referral hospital from Hospital of Subulussalam City based on a preliminary survey is varies. Inpatients are referred to Class A hospitals are on average 65%, Class B hospitals are 30%, and Class C hospitals are 5%, while outpatients are referred to Class A hospitals are on average 49%, Class B hospitals are 28%, class C hospitals are 23%. This type of research is qualitative with a phenomenological approach obtained by conducting in-depth interviews with 13 informants consisting of 3 specialist doctors, 3 general practitioners, 3 patients, 3 patient's family and 1 BPJS verifier in Hospital of Subulussalam City. The study was conducted from February to October 2018. The results showed that during the referral hospital decision-making process there was an interaction between the doctor, the patient and the patient's family, the final decision was on the patient and bearing down the consequences if the hospital's choice was not recommended by the doctor. The determinants of decision making for referral hospitals consist of perceived quality in the form of referral hospitals accepting patients referred from Hospital of Subulussalam City, emergency conditions for patients by choosing the closest hospital, facilities in the form of supporting tests and complete medical devices and additional facilities, the availability of specialist doctors and subspecialty according to the patient's condition, geographical constraints due to the long distance to the referral hospital, references from doctors to patients and vice versa, learning in the form of doctor and patient experience in the previous referral process, not all doctors consider peer relations to be a determinant of choosing a referral hospital due to the BPJS system, social factors in the form of a family in the area of ​​a referral hospital, the same religion and culture as a patient in a referral hospital area make the patient feel comfortable. Suggestions in this study is the management of Hospital of Subulussalam City to confirm and coordinate the referral hospital and make a referral MOU.